2021
DOI: 10.1007/s11042-021-11164-9
|View full text |Cite
|
Sign up to set email alerts
|

Phygital interfaces for people with intellectual disability: an exploratory study at a social care center

Abstract: Phygital interaction is a form of tangible interaction where digital and physical contents are combined in such a way that the locus of multimedia information is detached from the physical material(s) manipulated by the user. The use of phygital interaction is supported by several theoretical approaches that emphasize the development of cognitive skills dependent upon embodied interactions with the physical environment. Several studies demonstrate the potential of using phygital technologies for supporting peo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 53 publications
1
6
0
Order By: Relevance
“…With a specific focus on gaming, some studies (Lupetti et al, 2016;Mansilla et al, 2019) focused on technologies that combine physical objects with digital interfaces and online content. The result is smart resources capable of adapting to people's requirements, preferences, and routines in a reactive way (Gelsomini et al, 2021). Phygital applications also provide new resources for engaging customers and other actors, affecting their decision behaviour.…”
Section: Phygital Resources (Objects and Applications)mentioning
confidence: 99%
See 1 more Smart Citation
“…With a specific focus on gaming, some studies (Lupetti et al, 2016;Mansilla et al, 2019) focused on technologies that combine physical objects with digital interfaces and online content. The result is smart resources capable of adapting to people's requirements, preferences, and routines in a reactive way (Gelsomini et al, 2021). Phygital applications also provide new resources for engaging customers and other actors, affecting their decision behaviour.…”
Section: Phygital Resources (Objects and Applications)mentioning
confidence: 99%
“…The amalgamation of physical and digital contexts and spaces shapes a phygital space featured by the development of bonds, bridges, and webs that enable interaction and sharing between different human and non-human actors (Nakazawa & Tokuda, 2007;Shalini et al, 2021;Sustacha et al, 2022;Tolstikova et al, 2021). The phygital context provides a new form to connect and engage customers and support a smooth customer behaviour path (Gelsomini et al, 2021;Tolstikova et al, 2021). Banik (2021) argued that "phygital retail stores are investing tangible (e.g., physical and digital facilities) and intangible resources (e.g., information, status, pleasure) to receive favour from customers (e.g., engagement, patronage, referral)" (p. 8), influencing how a customer behaves along the journey The phygital context affects a customer journey that seamlessly integrates physical and digital experiences.…”
Section: Phygital Context (Space/place)mentioning
confidence: 99%
“…Numerous studies highlight the potential of tangible technologies in aiding individuals with intellectual disabilities, fostering the development of cognitive, sensorimotor, social, and behavioral skills (Antle & Wise, 2013;Falcão, 2017;Gelsomini et al, 2021;Beccaluva et. al., 2022).…”
Section: Inclusion and Tdstmentioning
confidence: 99%
“…Phygital interfaces, as introduced by Beaudouin-Lafon (2000), seamlessly blend digital and physical elements, ensuring a clear distinction between the display of digital information (e.g., on a screen) and the physical manipulation of objects by users. These interfaces leverage physical objects to serve a dual purpose: enabling user interaction to control digital elements, while also representing digital content through direct semantic mapping (Gelsomini et al, 2021).…”
Section: Tangible Digital Storytelling: the Fruitful Combination Of D...mentioning
confidence: 99%
“…In recent years, it has been observed that technology has been used more in special education research, especially with the use of video technology, and many skills have been taught (Cuturi, Cappagli, Yiannoutsou, Price, & Gori, 2022). Skills such as the ability to prepare and serve cold drinks, the teaching of simple first-aid skills in household accidents, the teaching of soup cooking game and first-aid game skills have been gained by using video technology (Gelsomini, Spitale, & Garzotto , 2021).…”
Section: Introductionmentioning
confidence: 99%